Pembuatan Aplikasi Monitoring Peminjaman Rekam Medis (Retrieval) Berbasis Microsoft Visual Basic 2010 di RSUD Dr. H. Andi Abdurrahman Noor Kabupaten Tanah Bumbu Tahun 2017 - Rina Gunarti; Dedy Rosyadi; Abdurrahman Abdurrahman (HB PRESS, 2018)
The medical record is documents containing notes such as patient identification, examination results, medication records, and other actions and services referred to by doctors or dentists regarding those actions to the patient in health services. Electronic Health Records (EHRs) is computerized activity contain medical and health records and electronization process related to it. This electronization produce systems specifically designed to support users with various facilities for the completeness and data accuracy, alerting instructions as warning, clinical decision support systems and linking data to medical knowledge and other tools. This study aimed to Creating a Application For Monitoring Borrowed Medical Records (Retrieval) by Microsoft Visual Basic 2010 at RSUD DR. H. Andi Abdurrahman Noor, Tanah Bumbu District in 2017. It was descriptive study method with qualitative approach. This study population was all information related to the borrowed medical record (Retriveal) application at RSUD DHAAN Tanah Bumbu District. This study, data analysis techniques used SDLC (Systems Development Life Cycle) or recycling system development. The observation results in outpatient and inpatient care filling room, the borrrowed medical records had not been using computerized system based on borrowed application, besides that the borrowed medical records were still manually with the recording method in medical record books borrowing.